Neurosurgical Training: Adapting to the New Normal - Thapa, Amit (Nepal Journal of Neuroscience, 2020)
The risk of transmitting COVID-19 infection while gathering in groups inside closed spaces and subsequent threat of morbidity and mortality among the health workers due to the disease, has forced medical education-programs globally to rethink and modify their mode of training. The neurosurgical training programs which have been built upon “read one, see one and do one” philosophy now seems impractical to pursue in wake of social distancing measures. Measures like re-scheduling of the duty rosters to keep the whole team from getting exposed, limit on number of health staff allowed inside operating rooms and in rounds, and curbs on amount of interactions with patients along with drastic reduction of routine operative cases in the hospitals, have made teaching and learning activities difficult.